(untitled) (Mūzikas akadēmijas raksti, 2024)
The article is devoted to determination of the style and classification of pianist-improvisers’ style. The aim of the publication is, basing on accessible literature, to consider the current ways of systematization and work out appropriate classification applicable to current performing art. Analyzing the individual manner of interpretation of a pianist, to my mind, we should draw a border between two basic spheres, in interaction 299 of which it is created, i.e. pianism (piano playing) and improvisation. Both spheres have their historical traditions. It in its turn gives the opportunity to illuminate the object of research in large enough context from the point of view of the 21st century, as well as to apply already known variants of classification of performing artists’ types.